How much of the macroeconomic variation in Eastern Europe is attributable to external shocks - Bartosz Maćkowiak (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
We decompose by origin the sources of the variation in real aggregate output and aggregate price level in the Czech Republic, Hungary and Poland. We find that a sizable fraction of the variation is attributable to external shocks, especially so for aggregate price level. We show that euroarea interest rate shocks can account for a significant fraction of the external spillover effects. We conclude that theoretical models of advanced transition economies and policy rules for these economies should feature a prominent role for external shocks.
Keywords: 330; Gesamtwirtschaftliche Produktion; Preisniveau; Schock; Zins; Tschechische Republik; Ungarn; Polen